Moderating Effect of Career Development for Employee Performance Supported by Work Placement and Social Capital - Nursaifullah - (Entrepreneurship Undergraduate Program at Amkop Business School, 2023)
For 150-200 word, An abstranct is a brief summary of a research article, thesis, review, conference proceeding or any-depth analysis of a particular subject or disipline, and is often used to help the reader quickly ascertain the paper purposes. When used, an abstract always appears at the beginning of a manuscript or typescript, acting as the point-of-entry for any given academic paper or patent application. Absatrcting and indexing services for various academic discipline are aimed at compiling a body of literature for that particular subject. Abstract length varies by di. scipline and publisher requirements. Abstracts are typically sectioned logically as an overview of what appears in the paper.